cultivating junior high school students critical thinking skills by using short-videos in english language classroom - Atayeva, Merjen - ((JELE) Journal Of English Language and Education, 2019)
An effective teaching method for cultivating students' critical thinking skills of junior high school students in Indonesia is very necessary as their critical thinking ability is still low. This research is a descriptive study which aimed at cultivating learners' critical thinking by using short-videos since it is believed that technology can motivate the students, increase their interest, engage them to the lesson matter, provide effective learning activities, and demand them to think critically and creatively. The subject in this study were 130 Junior High School students (SMP Negeri 1 Sedayu, Yogyakarta) grade IX. The students were homogeny in term of age, economic, and social background as well as in English language score. Facione's critical thinking rubrics were used to indicate the level of students' critical thinking such as their interpretation, analysis, evaluation, inference, explanation, and self-regulation skill of short video. The average score of all item in pre-test critical thinking skills was at fair level with the score 9 out of 20. The results indicate the students' interpretation skills were fair with the score of 9 out of 20; analytical skill was 12; evaluation skill was 9 out of 20; self-regulation was in fair criterion with the score of 5 out of 10 and good level of explanatory's skill with the score 6 out of 10, while 12 for inferences. It can be concluded that the critical thinking skill of the students of Junior High School was still unsatisfactory as most of them can only reach fair levels. The use of video cannot improve all critical thinking skills. It is recommended more practices for the students.